Effects of Milk and Milk-Product Consumption on Growth among Children and Adolescents Aged 6–18 Years: A Meta-Analysis of Randomized Controlled Trials. Issue 2 (6th March 2019) - Kang, Kai; Sotunde, Olusola F; Weiler, Hope A
ABSTRACT: Although studies have suggested that milk and milk-product consumption may influence growth during childhood and puberty, results are inconsistent. This meta-analysis was performed to evaluate the available evidence of randomized controlled trials (RCTs) assessing whether milk and milk-product consumption could affect growth and body composition among children and adolescents aged 6–18 y. PubMed, EMBASE, Web of Science, and The Cochrane Library databases were systematically searched for all RCTs published up to December 2017 that investigated milk and milk-product consumption (≥12 wk) on growth and body composition among participants (aged 6–18 y) without undernourishment or diseases. Study screening and data extraction by 2 reviewers followed established PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The Cochrane Collaboration's tool was used to assess the quality of the trials. Data were pooled using a random-effects model. Seventeen trials with 2844 children and adolescents were included. Milk and milk-product interventions resulted in a greater increase in body weight (0.48 kg; 95% CI: 0.19, 0.76 kg; P = 0.001), lean mass (0.21 kg; 95% CI: 0.01, 0.41 kg; P = 0.04), and attenuated gain in percentage body fat (−0.27%; 95% CI: −0.45%, −0.09%; P = 0.003) compared with control groups. However, there were no significant changes in fat mass, height, or waist circumference in the intervention groups compared with the control groups ( P ≥ 0.05). In subgroup analyses, the baseline weight and age, and the duration of intervention were associated with the efficacy of milk and milk-product intake on the change in lean mass, percentage body fat, and waist circumference, respectively (test for subgroup differences: P < 0.05). Children and adolescents aged 6–18 y consuming milk and milk products are more likely to achieve a lean body phenotype. This meta-analysis was registered in the International Prospective Register of Systematic Reviews (PROSPERO) as CRD42018086850.